2021
DOI: 10.1111/ced.14676
|View full text |Cite
|
Sign up to set email alerts
|

Narrowband ultraviolet B phototherapy is associated with a reduction in topical corticosteroid and clinical improvement in atopic dermatitis: a historical inception cohort study

Abstract: Background. Despite decades of use, the magnitude of efficacy of narrowband ultraviolet B (NB-UVB) phototherapy for atopic dermatitis (AD) beyond industrysponsored trials remains unclear. Aim. To evaluate the clinical efficacy of NB-UVB in AD under real-world conditions. Methods. We conducted a historical inception cohort study using automated recording of dispensed drugs to provide an objective treatment outcome in a large population catchment of 420 000 people over 15 years. We analysed clinical treatment ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“… 27 , 28 In chronic AD, it controls clinical signs, reduces bacterial colonization by Staphylococcus aureus ( S. aureus ) and Pityrosporum orbiculare, and improves insomnia, being a steroid-sparing measure as well. 27 , 29 , 30 …”
Section: Conventional Therapeutical Options For Admentioning
confidence: 99%
“… 27 , 28 In chronic AD, it controls clinical signs, reduces bacterial colonization by Staphylococcus aureus ( S. aureus ) and Pityrosporum orbiculare, and improves insomnia, being a steroid-sparing measure as well. 27 , 29 , 30 …”
Section: Conventional Therapeutical Options For Admentioning
confidence: 99%
“…Although IL-10 is implicated in the anti-inflammatory response, its role in AD has been interpreted as part of the predominant Th2 microenvironment, increased levels of IL-10 have been postulated to indirectly contribute to the AMP deficiency in patients with AD, potentially accounting for an increased propensity for infections. Higher IL-10 expression levels were reported in the skin of patients with chronic AD compared with the acute stage, possibly because of an upregulation of the receptors by interferon-gamma (IFN-γ) [ 49 , 50 ].Clinically, the effects of phototherapy have been further demonstrated by the fact that 70% of AD patients received significantly fewer TCS during the 12-month window after finishing NB-UVB, compared to the 12-month window before starting [ 51 ]. Phototherapy with medium-dose UVA1 irradiation exerts a significant antipruritic effect, decreases the severity of the disease, and improves the QoL of AD-affected patients.…”
Section: Atopic Dermatitis Treatmentmentioning
confidence: 99%
“…A large 2017 study that included 1,749 participants diagnosed with psoriasis found that 75% required less topical treatment 12 months after a clinic-based NBUVB treatment course (Foerster et al, 2017). Similarly, a 2021 multicenter, prospective cohort study of 844 patients with atopic dermatitis showed an overall reduction in topical corticosteroid use with the quantity dispensed reducing from 37.5 grams per month to 19.7 grams per month after the NBUVB treatment course (Choi et al, 2021). These studies analyzed data collected during routine care, similar to this study.…”
Section: Adjunct Medicationsmentioning
confidence: 99%